Penerapan Metode Paired Storytelling dan pengaruh terhadap Kemampuan Berbicara Bahasa Indonesia Siswa Sekolah Dasar - Nining Marlinda; Buyung Surahman; Wiji Aziz Hari Mukti (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Indonesian language instruction at the elementary school level aims to enhance students’ ability to communicate effectively both orally and in writing. However, many students still struggle with speaking skills, necessitating innovative and engaging teaching methods to support language development.Objective: This study aims to examine the effect of the Paired Storytelling method on the Indonesian speaking ability of elementary school students at SDN 24 Bengkulu City. Method: The research employed a Quasi-Experimental Design. It was conducted in 2023 at SDN 24 Bengkulu City. Data were collected using pre-tests and post-tests to measure students’ speaking abilities before and after the implementation of the Paired Storytelling method. Results: The findings revealed a noticeable improvement in students’ speaking abilities following the application of the Paired Storytelling method. This indicates that the method had a positive impact on students’ oral language performance. Conclusion: The Paired Storytelling method significantly enhances elementary students' speaking skills in Indonesian, making it an effective and interactive instructional approach.Contribution: This study contributes to the development of innovative teaching methods for language learning and can serve as a reference for future research exploring the use of Paired Storytelling in different educational settings and grade levels.